Percutaneous Coronary Intervention in Different Anomalous Coronary Arteries - An Observational Study (University Heart Journal, 2012)
Anomalous coronary arteries are uncommon but clinically significant, depending upon its ostial origin, course & distribution such patient may be asymptomatic or may present with angina, acute myocardial infarction, arrythmias, syncope & sudden cardiac death. Management of such cases may be medical, interventional & surgical as well. Some times it is difficult to cannulate such anomalous origin with conventional guiding catheters and requires different catheters unusual for such arteries. Between January 2002 to June 2012 a total of 3,110 elective PCI procedure were performed in NICVD & other cardiac centers in Dhaka, out of which twentyone cases were in different varities of anomalous coronary artery. We report here successful PCI in twenty-one cases having eight verities of abnormal coronary artery with failure in one case. Percutaneous coronary intervention of anomalous coronary artery origins may be difficult, which require appropriate catheter selection and different tricks. Success depends on patience and careful decision of the operator. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11663 University Heart Journal Vol. 8, No. 1, January 2012